USING DIRECTIONAL AND HYPERSPECTRAL REMOTE SENSING OBSERVATIONS FOR IMPROVING CROP CLASSIFICATION - Lúcia Costa Alves Soua, Vânia (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
Mapping accurately agricultural fields is one of the main challenges for monitoring areas using remote sensing. Crops change during the growing season and it is often desirable to use images acquired at several dates for plant identification. However, there is a high cost for these image acquisitions. Airborne or satellite campaigns usually cover specific regions for specific dates then offering limited data. Advances in sensor technologies created hyperspectral sensors to overcome this spectral limitation of multispectral sensors.